2012
DOI: 10.1007/s11005-012-0551-z
|View full text |Cite
|
Sign up to set email alerts
|

Regularity for Eigenfunctions of Schrödinger Operators

Abstract: We prove a regularity result in weighted Sobolev (or Babuška-Kondratiev) spaces for the eigenfunctions of certain Schrödinger-type operators. Our results apply, in particular, to a non-relativistic Schrödinger operator of an N -electron atom in the fixed nucleus approximation. More precisely, let K m a (R 3N , r S ) be the weighted Sobolev space obtained by blowing up the set of singular points of the potentiala for all sm ∈ Z + and all a ≤ 0. Our result extends to the case when b j and c ij are suitable bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(84 citation statements)
references
References 54 publications
5
79
0
Order By: Relevance
“…See [6] for the definition of Lie manifolds with boundary. General blow-up procedures for Lie manifolds were studied in [5]. It can be shown that the class of Lie manifolds satisfying Theorem 4.14 is closed under blow-ups with respect to tame Lie submanifolds.…”
Section: 4mentioning
confidence: 99%
“…See [6] for the definition of Lie manifolds with boundary. General blow-up procedures for Lie manifolds were studied in [5]. It can be shown that the class of Lie manifolds satisfying Theorem 4.14 is closed under blow-ups with respect to tame Lie submanifolds.…”
Section: 4mentioning
confidence: 99%
“…The set of inward pointing vectors in v ∈ T x (M ) will form a closed cone denoted T + x (M ). If, close to x, our manifold with corners is given by the conditions {f i (y) ≥ 0} with df i linearly independent at x, then the cone T + x (M ) is given by (1) T…”
Section: Preliminaries On Lie Algebroidsmentioning
confidence: 99%
“…Proof. The proof follows the lines of the proof of Theorem 3.10 in [1], using the A-tameness of L in order to construct the Lie algebra structure on Γ(M ; A). We include the details for the benefit of the reader, taking also advantage of the results in Subsection 1.2.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…6. A interesting alternate approach to understanding the Kato cusp conditions in terms of singularities at corners is found in Ammann et al [11].…”
Section: As Withmentioning
confidence: 99%